Genome analysis uncovers an inverse correlation between alterations in P21‐activated kinases and patient survival across multiple cancer types - Jessie M. Vo; Linh M. La; Ananda V. Anderson; Abdulaziz H. Alanazi; Payaningal R. Somanath (Physiological Reports)
Abstract Cancer is a complex disease with profound societal and economic impacts, especially in metastatic cases where treatment challenges arise due to the absence of reliable biomarkers and effective therapies. While P21‐activated kinases (PAKs) play a key role in cancer progression, their potential as predictive markers for metastasis and therapeutic targets has not been fully explored. We hypothesized that genetic alterations in PAK isoforms could be linked to reduced overall patient survival. To investigate this, we used data from the cBioPortal for Cancer Genomics, analyzing several randomized, multicentered phase‐3 clinical trial datasets. The analysis revealed significant genetic alterations in PAK genes, particularly in cancers such as breast, prostate, pancreatic, and lung. Notably, elevated PAK expression was associated with poorer survival outcomes in prostate and breast cancer patients. In pancreatic and lung cancers, although a trend of poorer survival with PAK alterations was observed, it was not statistically significant. Our findings underscore the importance of PAK isoforms as potential biomarkers and therapeutic targets, particularly in metastatic cancers. Further research could lead to improved patient outcomes through targeted interventions aimed at PAK‐related pathways, with PAK serving as a reliable biomarker for the precise diagnosis, monitoring, and personalization of treatment strategies.